2019
DOI: 10.2147/cmar.s190966
|View full text |Cite
|
Sign up to set email alerts
|

<p>Feasibility of computer-assisted diagnosis for breast ultrasound: the results of the diagnostic performance of S-detect from a single center in China</p>

Abstract: ObjectiveTo investigate the feasibility of a CAD system S-detect on a database from a single Chinese medical center.Materials and methodsAn experienced radiologist performed breast US examinations and made assessments of 266 consecutive breast lesions in 227 patients. S-detect classified the lesions automatically in a dichotomous form. An in-training resident who was blind to both the US diagnostic results and histological results reviewed the images afterward. The final histological results were considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 23 publications
(29 reference statements)
5
42
0
Order By: Relevance
“…Second, in the aspect of intralesional calcification, we only studied the value of the number of calcification in the differential diagnosis of BI-RADS 4A benign and malignant lesions, but the significance of the size and shape of calcification in the differential diagnosis was not clear. Finally, this study was based on manually contoured images for quantitative analyses of ROI, which was different from other studies that focused on lesions that are automatically contoured by AI [26]. The present study did not evaluate the automatic identification efficiency for BI-RADS 4A lesions of our AI diagnosis system, and these aspects will be studied in the future.…”
Section: Discussionmentioning
confidence: 90%
“…Second, in the aspect of intralesional calcification, we only studied the value of the number of calcification in the differential diagnosis of BI-RADS 4A benign and malignant lesions, but the significance of the size and shape of calcification in the differential diagnosis was not clear. Finally, this study was based on manually contoured images for quantitative analyses of ROI, which was different from other studies that focused on lesions that are automatically contoured by AI [26]. The present study did not evaluate the automatic identification efficiency for BI-RADS 4A lesions of our AI diagnosis system, and these aspects will be studied in the future.…”
Section: Discussionmentioning
confidence: 90%
“…Second, although there were signi cant differences between the benign group and malignant group in regard to margin lobules, entropy, internal calci cation and ALS, a cut-off value for differential diagnosis between these two groups was not obtained. This study was based on manually contoured images for the performance of quantitative analyses of ROI, which is different from other studies that focus on lesions that are automatically contoured by AI [20].The present study did not evaluate the automatic identi cation e ciency for BI-RADS 4A lesions of our AI diagnosis system, and these aspects will be studied in the future.…”
Section: Discussionmentioning
confidence: 90%
“…This system has good performance in diagnosing benign and malignant breast lesions and especially in improving the specificity of ultrasound (8). Our early study showed that the deep learning-based CAD had the same diagnostic accuracy as experienced radiologists, and the specificity of the CAD was higher than that of the radiologists, which helped to reduce the number of unnecessary biopsies (9). Our recent study also showed that the deep learning-based CAD had a better performance in the breast benign lesions than the radiologists, especially in fibroadenomas and adenosis (10).…”
Section: Introductionmentioning
confidence: 93%
“…The deep learning-based CAD system used in our study (Samsung corporation, Seoul Korea) is a newly developed CAD system for breast ultrasound based on deep learning of raw ultrasound signals through a convolutional neural network. After extensive learning and training on a large number of databases, the deep learning-based CAD system could extract high-order statistics and optimize the balance of input and output data through multiple hidden layers to provide an accurate diagnosis (9). The original unprocessed ultrasound signals were collected as the raw data and information for the deep learning-based CAD system to analyze through a complex hierarchical framework.…”
Section: The Role Of Deep Learning-based Cad System In the Breast Lesmentioning
confidence: 99%